Management of Large Scale Thesis Production - Larsson, Ken (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2018)
This study focuses on investigating several parameters that may influence the production of student theses in a University setting. This knowledge is valuable in determining future changes in any of the parameters that may influence the production and quality of the graduation work at the department. During the period of the study, there have been several changes in the process of thesis writing at the department, trigged by internal and external factors. The analysis has been done in steps where new variables have been calculated from other variables, for instance, the number of days from start to finish. There is no exact way of measuring this period so in the study the start date is considered to be the date of the students registering for the thesis course, the completion date is set to be the date of the last grade of the project. On the aggregated level three variables have been studied to determine the change over time, completion rates, change in grades and the time it takes for a student from registration to completion. During the studied period, projects started from 2010 and through to 2014; there is noticeable a sharp increase of noncompeting between 2011 and 2012. One reason for this could be the introduction of new grading criteria, but the increases are not dropping off but continue to rise. Projects started in 2010 have a non-completion rate of about 17 percent, for projects started in 2014 has this increased to about 42 percent. The time from the start to completion has increased during the studied period, from an average of 175 days in 2010 to 331 in 2014. There is a sharp increase in the length to completion in 2012, possibly caused by the introduction of a new grading process. A total of 47 supervisors fulfilled the requirements of the study by starting at least ten projects in the period of this analysis. Twenty-eight of the supervisors have at least 50 percent completion rate, this group of supervisors also have a shorter time to completion, on an average 319 days as compared with the group that has lower completion rate the average time to completion is 399 days. Recommendations from this study are in three separate strategies: recommendations on a viable process for improvement of the production process, recommendations on immediate changes in management directives regarding supervision and finally recommendations towards a new management style in general.